Travail, mobilités, subjectivités et Formes d'assujettissement dans les Amériques - Martig, Alexis; Pantaleón, Jorge F. (Collection Nord-Sud (Québec, Québec), 2019)
[Machine translated] Based on various geographic, social and political approaches and contexts, this book introduces the reader to the complexity and diversity of reflections on the forms of labor exploitation experienced by workers in migration and mobility situations in the Americas. To do this, texts that dialogue, echo and complement one another in order to provide readers with a reflexive framework formed from different central concepts to capture the subject matter, while presenting the plurality of actors involved: migrant workers, states, migrant smuggling networks, employment agencies, private companies, employers. In order to allow transversal readings of the texts gathered here and to grasp the nuances and contradictions experienced by the workers, the book was organized around the heuristic relationships between the three couples of the following notions: mobility (s) / immobility (s); coercion / consent; precariousness / improvements in living conditions.